Perlindungan Hukum Konsumen dalam Perjanjian Jasa Pengiriman Barang pada PT. Tiki Jalur Nugraha Ekakurir Agen Bedahan, Sawangan, Depok, Jawa Barat - Dio Dharmawan; Abdurrauf Abdurrauf (JOURNAL of LEGAL RESEARCH, 2021)
The research focuses more on the procedures for conducting goods and service delivery agreements carried out by PT Tiki Jalur Nugraha Ekakurir as well as the process of compensation for goods and services delivery. The research method used in this research is normative juridical with a statutory approach and a conceptual approach to data sources obtained from primary legal materials, secondary legal materials and non-legal materials. From the results of this research, it can be concluded that according to Consumer Protection as stated in Article 1 Paragraph (1) of Law Number 8 Year 1999, consumer protection is any effort that ensures legal certainty to provide protection to consumers as regulated in Article 7 paragraph (7). ) Law Number 8 of 1999 concerning Consumer Protection which regulates the provision of compensation and compensation.Keywords: Consumer Protection, Delivery of Goods, PT. Tiki Nugraha Ekakurir Line